(untitled) (Journal of Engineering, 2024)
Modified asphalt is considered one of the alternatives to address the problems of deficiencies in traditional asphalt concrete, as modified asphalt addresses many of the issues that appear on the pavement layers in asphalt concrete, resulting from heavy traffic and vehicles loaded with loads that exceed the design loads and the large fluctuations in the daily and seasonal temperatures of asphalt concrete. The current study examined the role of polyphosphoric acid (PPA) as a modified material for virgin asphalt when it was added in different proportions (1%, 2%, 3%, 4%) of the asphalt weight. The experimental program includes the volumetric characteristics associated with the Marshall test, the physical properties, and the FTIR spectroscopy examination of virgin asphalt and polyphosphoric acid (PPA) modified asphalt. This study showed that mixtures with modified asphalt using polyphosphoric acid (PPA) by 3% achieved the typical Marshall properties at the optimal asphalt content of 4.8%, recording a 10% decrease in the optimum asphalt content for the mixtures made with virgin (unmodified) asphalt, whose proportion was 4.9% is the optimum asphalt content. PPA is available in the local markets and is considered cheaper than polymers. It is also regarded as economical as it reduces the optimum content of asphalt.